Studying the section «Basic properties of a function» using computer programs for the development of knowledge and activity - Kosybaeva, U.А.; Kauymbek, I.S.; Shegirova, D.К.; Mikhailova, N.B. (Publ.KarSU, 2017)
In the article it is analyzed one of the main subjects of the algebra which studied at high secondary general school. The intersubject communication and use of computer programs used in the course of training of a subject is estimated. Authors of article show relevance of use of the training computer programs used for development of knowledge and skills in pupils. And also in article use of the animation Flash program is analyzed. The article deals with the improvement of the methodology of teaching mathematics in secondary schools. The methodology of teaching mathematics using special computer programs along with the traditional method of teaching makes it possible to explain more deeply the specific subtleties of a difficult school subject. However, many kinds of such special computer programs leave a choice for the teachers of the subject and this requires the teacher knowledge in this area. In this article, a program analysis is provided to help the teacher. Using the capabilities of programs such as MathCad, MS Flash gives the math teacher the opportunity to create animated material for such complex topics as the rotation of geometric figures, the point of intersection of figures, etc. However, the practice of using such programs by teachers in math lessons improves the methodology of teaching mathematics.
Білім мен белсенділікті дамыту үшін «Функцияның негізгі қасиеттері» бөлімін компьютерлік бағдарламалар көмегімен оқып үйрету
Изучение раздела «Основные свойства функции» с использованием компьютерных программ для развития знаний и деятельности
Keywords: mathematics; methodology; computer programs; traditional teaching methods; active teaching methods; special program; training; learning outcomes; private methodology; animation program